Oncogenic Ras deregulates cell-substrate interactions during mitotic rounding and respreading to alter cell division orientation - Ganguli, Sushila (Curr Biol, 2023)
Oncogenic Ras has been shown to change the way cancer cells divide by increasing the forces generated during mitotic rounding. In this way, Ras(V12) enables cancer cells to divide across a wider range of mechanical environments than normal cells. Here, we identify a further role for oncogenic Ras-ERK signaling in division by showing that Ras(V12) expression alters the shape, division orientation, and respreading dynamics of cells as they exit mitosis. Many of these effects appear to result from the impact of Ras(V12) signaling on actomyosin contractility, because Ras(V12) induces the severing of retraction fibers that normally guide spindle positioning and provide a memory of the interphase cell shape. In support of this idea, the Ras(V12) phenotype is reversed by inhibition of actomyosin contractility and can be mimicked by the loss of cell-substrate adhesion during mitosis. Finally, we show that Ras(V12) activation also perturbs division orientation in cells cultured in 2D epithelial monolayers and 3D spheroids. Thus, the induction of oncogenic Ras-ERK signaling leads to rapid changes in division orientation that, along with the effects of Ras(V12) on cell growth and cell-cycle progression, are likely to disrupt epithelial tissue organization and contribute to cancer dissemination.